2012
DOI: 10.2105/ajph.2012.300686
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal, Perinatal, Early Life, and Sociodemographic Factors Underlying Racial Differences in the Likelihood of High Body Mass Index in Early Childhood

Abstract: Objectives We investigated early childhood disparities in high body mass index (BMI) between Black and White US children. Methods We compared differences in Black and White children’s prevalence of sociodemographic, prenatal, perinatal, and early life risk and protective factors; fit logistic regression models predicting high BMI (≥ 95th percentile) at age 4 to 5 years to 2 nationally representative samples followed from birth; and performed separate and pooled-survey estimations of these models. Results A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 62 publications
(95 reference statements)
5
54
2
Order By: Relevance
“…We test and substantiate the validity of this assumption by conducting diagnostics under a model-fitting framework (see Rendall et al 2013; Weden et al 2012). Our finding of model-fit improvement when adding an intercept shift variable for overall child obesity level differences between the surveys, we argue, is not problematic (for further discussion, see Baker et al 2012: appendix).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…We test and substantiate the validity of this assumption by conducting diagnostics under a model-fitting framework (see Rendall et al 2013; Weden et al 2012). Our finding of model-fit improvement when adding an intercept shift variable for overall child obesity level differences between the surveys, we argue, is not problematic (for further discussion, see Baker et al 2012: appendix).…”
Section: Methodsmentioning
confidence: 95%
“…Similarly, using the ECLS-B data, but for non-Hispanic white and black children only, Weden et al (2012) estimated a quadrupling of the child's odds of obesity when the mother was obese relative to normal weight status. Hamilton et al (2011b), analyzing Mexican-origin children at age 9 in the FFCWS, found that having an obese mother quintupled the odds of the child's being obese relative to having a normal-weight mother.…”
Section: Evidence Regarding An Immigrant Epidemiological Paradox For mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, African-American children have a prevalence of being overweight when compared to Caucasian children. 50,51 Whitaker and Orzol 52 found that race/ ethnicity and other SES indicators did not explain the higher rates of obesity in Hispanic children when compared to Caucasian or African American children. Other studies reported in the literature have shown similar conflicting results.…”
Section: Sleepmentioning
confidence: 96%
“…Childhood weight status often continues into adulthood and is a risk factor for later diabetes, heart disease, and hypertension(Maffeis and Tato 2001, Han, Lawlor and Kimm 2010, Reilly and Kelly 2001, Franks et al 2010.). Furthermore, minority children are disproportionally affected by higher rates of obesity with 35.2% of Non-Hispanic black children classified as overweight and 20.2% classified as obese compared to their white counterparts with 28.5% classified as overweight and 14.1% classified as obese (Ogden et al 2014, Weden, Brownell and Rendall 2012). With a number of factors contributing to the high rates of obesity in African American youth, understanding their current diet quality and contributions to diet quality is of importance.…”
Section: Introductionmentioning
confidence: 99%